A new species of Brachionidium (Pleurothallinidae) from the Yanachaga Chemillen National Park, Pasco, Peru - Valenzuela Gamarra, Luis (2023)
A new Brachionidium from Peru is described and illustrated. The new species, B. montieliae,was discovered in one of the highest mountains of the Oxapampa-Ashaninka-Yanesha Biosphere Reserve (BIOAY), situated above the forests of the humid puna of the Yanachaga Chemillen National Park at 3590 m in elevation. It is similar to Brachionidium vasquezii but differs in the oblong-elliptic, denticulate, and semi-erect leaves, somewhat lanuginose abaxially; the purple lanuginose adaxially and papular abaxially, entire, acuminate lateral sepals; the purplish oblong-ovate dorsal sepal, lanuginose on the adaxial surface, papular abaxially; the purple petals with scalloped edges, acuminate to obtuse apex ending in a thin, slightly abbreviated tail; the lip with apiculate lateral angles and with a central, trapezoid verrucose callus on the disc. Brachionidium montieliae is a terrestrial species that thrives in the humid Puna forests at elevations around 3400-3600 meters. The ecosystem is characterized by a sclerophyllous forest with a diverse range of tree species. Information on distribution, ecology, etymology, and phenology is also included. There are potential threats from annual burning practices in the region. Given the potential risks, it is imperative to undertake immediate conservation measures and promote environmental awareness to safeguard this species.
Se describe e ilustra un nuevo Brachionidium del Perú. La nueva especie, B. montieliae, fue descubierta en una de las montañas más altas de la Reserva de Biósfera Oxapampa-Asháninka-Yánesha (BIOAY), situada sobre los bosques de la puna húmeda del Parque Nacional Yanachaga Chemillén a 3590 m de elevación. Es similar a Brachionidium vasquezii pero se diferencia en las hojas oblongo-elípticas, denticuladas y semierectas, algo lanuginosas hacia el envés; los sépalos laterales púrpuras, con el borde entero, acuminados, lanuginosos hacia el haz y papulados hacia el envés; el sépalo dorsal oblongo-ovado de color púrpura, lanuginoso hacia el haz y papulado hacia el envés; los pétalos púrpuras, bordes festoneados, con el ápice acuminado obtuso, terminando en una cola delgada y corta; el labelo con los ángulos laterales apiculados, con un callo central, trapezoide y verrucoso sobre el disco. Brachionidium montieliae es una especie terrestre que prospera en los bosques de puna húmeda entre los 3400 a 3600 metros de elevación. El ecosistema se caracteriza por ser un bosque esclerófilo con una gran diversidad de especies arbóreas. También se incluye información sobre distribución, ecología, etimología y fenología. Existen amenazas potenciales por las prácticas de quema anual en la región. Dados los riesgos potenciales, es imperativo emprender medidas de conservación inmediatas y promover la conciencia ambiental para salvaguardar esta especie.
Keywords: ORQUIDEAS -- IDENTIFICACION -- PERU; ORQUÍDEAS -- CONSERVACIÓN -- PERÚ